Role of ATP hydrolysis in the DNA translocase activity of the bovine papillomavirus (BPV-1) E1 helicase - Castella, Sandrine (Oxford University Press, 2006)
The E1 protein of bovine papillomavirus type-1 is the viral replication initiator protein and replicative helicase. Here we show that the C-terminal ∼300 amino acids of E1, that share homology with members of helicase superfamily 3 (SF3), can act as an autonomous helicase. E1 is monomeric in the absence of ATP but assembles into hexamers in the presence of ATP, single-stranded DNA (ssDNA) or both. A 16 base sequence is the minimum for efficient hexamerization, although the complex protects ∼30 bases from nuclease digestion, supporting the notion that the DNA is bound within the protein complex. In the absence of ATP, or in the presence of ADP or the non–hydrolysable ATP analogue AMP–PNP, the interaction with short ssDNA oligonucleotides is exceptionally tight (T(1/2) > 6 h). However, in the presence of ATP, the interaction with DNA is destabilized (T(1/2) ∼60 s). These results suggest that during the ATP hydrolysis cycle an internal DNA-binding site oscillates from a high to a low-affinity state, while protein–protein interactions switch from low to high affinity. This reciprocal change in protein–protein and protein–DNA affinities could be part of a mechanism for tethering the protein to its substrate while unidirectional movement along DNA proceeds.